Assessment of the severity of malocclusion and orthodontic treatment needs among 16-24-year-old rural population of Dehradun, India: A cross-sectional study - Amit Rekhi; Amit Mehra; Yashika Saini (Wolters Kluwer Medknow Publications, 2016)
Introduction: Malocclusion is a developmental condition signifying a mal-relationship between the arches. It is classified into several types and manifest variably from person to person. Aim: To evaluate the severity of the malocclusion and orthodontic treatment needs in 16-24-year-old Indian young adults. Materials and Methods: A cross-sectional study was conducted among 660 subjects (352 males; 308 females) residing in rural areas of Dehradun, India. Clinical examinations were conducted using the dental esthetic index (DAI) to evaluate the extent of orthodontic treatment needs among the population. Results: The mean DAI score of the sample was found to be 31.08 ± 7.98. No gender-wise differences were found. Statistically significant differences were observed between the age groups. Diastema between males and females was the only component where differences were found to be statistically significant. Conclusion: Around 45.15% of the total sample had a highly desirable and mandatory orthodontic treatment need. Gender did not influence treatment need whereas age group was found to influence it.